Proteomics and bioinformatics analysis of mouse hypothalamic neurogenesis with or without EPHX2 gene deletion - Zhong, Lijun (Int J Clin Exp Pathol, 2015)
The aim of this study was to identify differently expressed proteins in the presence and absence of EPHX2 gene in mouse hypothalamus using proteomics profiling and bioinformatics analysis. This study was performed on 3 wild type (WT) and 3 EPHX2 gene global knockout (KO) mice (EPHX2 (-/-)). Using the nano- electrospray ionization (ESI)-LC-MS/MS detector, we identified 31 over-expressed proteins in WT mouse hypothalamus compared to the KO counterparts. Gene Ontology (GO) annotation in terms of the protein-protein interaction network indicated that cellular metabolic process, protein metabolic process, signaling transduction and protein post-translation biological processes involved in EPHX2 (-/-) regulatory network. In addition, signaling pathway enrichment analysis also highlighted chronic neurodegenerative diseases and some other signaling pathways, such as TGF-beta signaling pathway, T cell receptor signaling pathway, ErbB signaling pathway, Neurotrophin signaling pathway and MAPK signaling pathway, were strongly coupled with EPHX2 gene knockout. Further studies into the molecular functions of EPHX2 gene in hypothalamus will help to provide new perspective in neurogenesis.